Effect of silicon content on wear resistance and corrosion behaviour of Al-Si eutectic alloy - Korkut, M. H.; Eren, H. (Taylor & Francis Ltd, 2007)
In the present study, Al-Si eutectic alloys produced at the Aluminium Institution were studied. The alloys were cast and forged into bars of 20 mm diameter. The results obtained were compared with a pure aluminium sample. Metallographic analysis, spectral analysis, SEM and energy dispersive spectroscopy analysis, pin on disk abrasive wear tests and mass loss tests were performed. Wear resistances of alloys with various silicon contents were tested under different loads and constant abrasive speed. SiC abrasive paper of 80 grit size was used. The dry sliding tests were carried out under loads of 10, 20 and 30 N and the testing was conducted under a constant sliding velocity of 36.8 m min(-1) in a dry air atmosphere. Corrosion rates were determined in 0.1M NaCl acid solutions. The corrosion tests were performed at 2, 4, 6 and 8 h. The wear and corrosion resistance of all the eutectic alloys increased with increasing silicon content in the matrix.
Keywords: Abrasive wear; SiO2; Al-Si eutectic; Corrosion